Karl Popper and the methodologists of economics. (5th October 2016) - Thomas, Rod
Abstract: This article chronicles the difficulties that methodologists of economics have had in introducing Karl Popper's philosophy to their fellow economists. It presents some general reasons for the problem before specifically examining the proposition that a sound appreciation of Popper's doctrines cannot be attained from simply studying the doctrines themselves. What it also requires is an understanding of the problem situation that the doctrines sought to address. This is illustrated through an examination of the way methodologists have grasped, or failed to grasp, the development of Popper's own thought about the problem of demarcating empirical science from non-science and the related problem of whether the limits of empirical science coincide with the limits of arguability. The article demonstrates that a neglect of these considerations has produced confusion in the literature, both in the way that Popper's philosophy has been presented and in the way in which its contemporary relevance has been assessed.